Students’ English Structure and Written Competence - Palentja Etta Tilana; Wisma Yunita; Zahrida . (Journal of English Education and Teaching, 2019)
This research aims to investigate the students’ English competence, the highest percentage of students’ mistake and their difficulties in responding to the TOEFL structure and written expression sections. All of the 6th semester students of the English Education Study Program of Universitas Bengkulu who had passed all structure courses were involved in this research. The data were collected through a TOEFL test and an interview. The results show that majority of the students’ English competence was poor. It also reveals that the most difficult topic in grammar section was redundancy. There were two factors that affected the students’ performance in redundancy, ambiguity and the interference of first language. In contrast, gerund and infinitives were the easiest topic in grammar section. Simple rules and the most common expression were contributed to the students’ performance in gerund and infinitives. In responding to structure and written expression section there were four factors that influenced students’ difficulties, poor understanding of grammar, less focus, lack of practice and limited vocabulary.